PEMODELAN DEBIT BANJIR SEHUBUNGAN DENGAN PREDIKSI PERUBAHAN TUTUPAN LAHAN DI DAERAH ALIRAN CI LEUNGSI HULU MENGGUNAKAN HEC-HMS - Marko, Kuswantoro; Zulkarnain, Faris (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2018)
Upper Ci Leungsi catchment area is one of the catchments that has an important role in contributing water runoff to downstream areas i.e. Bekasi City. High population growth has led to significant changes in land use that impact in potentially increased surface runoff causing flooding. This study aims to estimate the flood discharge that will occur in relation to land cover change prediction in 2020, 2025, and 2030. The SCS-CN method is used for calculation of runoff volume and synthetic unit hydrograph using HEC-HMS. The CN value obtained on the existing data i.e. 72.5; 74.4; and 75.4 in 2005, 2010, and 2014 respectively, whereas the predicted CN values in 2020, 2025 and 2030 increased by 77.2; 78.4; and 79.4 respectively. This study concludes that the prediction of flood discharge in 2020, 2025, and 2030 has increased, from 2020 to 2025 by 28.4%, and from 2025 to 2030 by 26.8%. For a 25-year re-period with 197mm design rainfall resulted in flood discharge of 624.6, 653.0, and 679.8 m3 / dt in 2020, 2025, and 2030 respectively. This study is highly useful for urban development planning, particularly in anticipating the damages due to floods in future.